The Quartz Veins, Hydrothermal Alteration and Ore Mineralization of Orogenic Gold Deposit at Mendoke Mountains, Southeast Sulawesi, Indonesia - Hasria, Hasria (Union of Iraqi Geologists, 2022)
The research at Mendoke Mountains, Southeast Sulawesi Province, particularly for the study of gold deposits, becomes a new challenge because there is no previous detailed study. This study aims to analyze the characteristics of orogenic gold deposits, which include the type and texture of quartz veins, alteration and hydrothermal mineralization with hosted metamorphic rocks. The research methods used include fieldwork and laboratory analysis. The type and texture of quartz veins were identified based on the field observations. The hydrothermal alteration was analyzed using X-ray diffraction analysis, and hydrothermal mineralization which analyzed by ore microscopy. The results showed that there are three types of quartz veins parallel and crosscut to the direction of foliation, and laminated quartz veins. The quartz veins’ texture is deformed, segmented, brittle, sheared, laminated, sheeted, irregular veins, brecciated, massive and sigmoidal. The hydrothermal alteration consists of sericitization, argillic, propylitic and carbonization alterations. The hydrothermal mineralization consists of native gold, chalcopyrite, pyrite, stibnite, covellite, cinnabar, galena, arsenopyrite, chrysocolla, magnetite, hematite and goethite. The host rock of gold mineralization in the study area is classified into the greenschist facies. Based on these characteristics, it shows that gold deposits in the Mendoke Mountains are orogenic gold deposits. © 2022, Union of Iraqi Geologists. All rights reserved.